Integrasi Servicescape, HEALTHQUAL, dan Model Kano dalam Evaluasi Pengalaman Pasien Griya Sehat UKDC Surabaya - Nyoman Sri Widari; Desrina Yusi Irawati; Fidelchristo Pijoh (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2026)
The growing demand for holistic healthcare services requires comprehensive evaluation of service quality beyond therapeutic outcomes. This study examines patient experience in acupuncture and herbal services at Griya Sehat UKDC by integrating servicescape and HEALTHQUAL dimensions and classifying service attributes using the Kano model to determine improvement priorities. A case study design with a survey approach was conducted involving 32 patients. Data were collected through paired functional and dysfunctional Kano questionnaires, followed by validity and reliability testing. The results show that 76.3% of service attributes fall into the one-dimensional category, indicating that patient satisfaction is primarily driven by service performance. Therapist competence, safety assurance, empathy, cleanliness, and treatment efficiency emerge as critical determinants. These findings suggest that improving core service execution has a direct linear impact on patient satisfaction in holistic healthcare settings.